Diversity of mosquito species (Diptera: Culicidae) in the residential area and rice field of Kampung Rembus, Samarahan division, Sarawak, Malaysia - Siew, Fui Wong; Yee, Ling Chong; Kuok, Freddy San Yeo (Penerbit Universiti Kebangsaan Malaysia, 2024)
The information on the distribution and occurrence of mosquito species is crucial for anticipating the prevalence of mosquito borne diseases. The surveillance data of mosquitoes for Sarawak continues up to recently. Anthropogenic activities provide breeding grounds for mosquitoes. For example, a flooded wetland rice field created an artificial aquatic habitat for mosquitoes. In Sarawak, Malaysia no data is available on the occurrence of mosquito species in wetland rice fields so far. The objective of this study was to document the diversity of mosquitoes in the rice field and residential area of Kampung Rembus, Sarawak, Malaysia during the early stages of the rice planting season. Ten plastic containers containing one litre of rainwater were placed permanently in the residential area and rice field, respectively. All mosquito larvae and pupae were collected from every plastic container once a week and identified. The water temperature, ambient temperature and relative humidity were monitored during the study. A total of four BG-Sentinel trap baited with BG-Lure were also set in the residential area and rice field. The trapped adult mosquitoes were identified and counted. Eight mosquito species from six genera were recorded in the present study namely Aedes albopictus, Culex quinquefasciatus, Culex fuscocephala, Culex pseudovishnui, Coquillettidia sp., Uranotaenia maxima, Toxorhynchites indicus and Lutzia fuscanus. A total of 4,756 individuals were encountered in residential areas and 1,390 individuals from rice field. The highest number of mosquito species collected was Ae. albopictus with 4,515 individuals at the study sites. The two mosquito species with the lowest number of individuals were Cx pseudovishnui and Coquillettidia sp. with only one individual collected during a three-month study. Aedes albopictus, Cx quinquefasciatus, Cx fuscocephala and Cx pseudovishnui are recorded for the first time in the rice field of Sarawak. Aedes albopictus and Cx. quinquefasciatus showed a weak correlation with ambient temperature and relative humidity. However, both species demonstrated a strong correlation with water temperature. Our findings are the first report for the study area and for the rice field of Sarawak. There were mosquito species which are vectors of mosquito borne diseases. To prevent the spread of mosquito borne diseases among residents in Kampung Rembus, it is crucial to continuously monitor and manage mosquito breeding sites.